ML-09 DIAGNOSIS AND TREATMENT OF PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA IN HIV POSITIVE PATIENTS. (16th December 2019) - Takano, Koji; Nishimoto, Keisuke; Yamazaki, Hiroki; Murakami, Koki; Tachi, Tetsuro; Kidani, Tomoki; Kanemura, Yonehiro; Nakajima, Shin; Masuda, Tomohito; Kurusu, Tomomi; Hirota, Kazuyuki; Uechi, Takashi; et al.
Abstract: INTRODUCTION: HIV infection is known to cause a variety of central nervous system complications, such as malignant lymphoma (ML), toxoplasma encephalopathy, cryptococcal encephalopathy, progressive multifocal leukoencephalopathy (PML), brain tuberculosis and HIV encephalopathy. In our hospital, we performed brain biopsy for HIV-positive patients with central nervous system lesions suspected malignant lymphoma, or cases difficult to diagnose with blood, cerebrospinal fluid, and imaging alone. In this study, we retrospectively examined HIV-positive patients who underwent brain biopsy at our hospital, and analyzed diagnosis and treatment of patients with ML. Methods HIV-positive patients who underwent brain biopsy in our hospital from January 2010 to April 2019 were examined in this study. We analyzed background factors, preoperative examination results, pathological diagnosis, treatment and prognosis. RESULTS: There were 1, 894 HIV-positive patients who were treated at our hospital during the period, of which 16 cases underwent a total of 18 brain biopsies. The final diagnosis was 7 ML (6 PCNSL, 1 brain metastasis), 3 toxoplasma encephalopathy, 1 PML, 1 brain tuberculosis, 1 immune reconstitution syndrome, 1 Penicillium marneffei infection, 1 hematoma and one case that could not be diagnosed. In patients with ML, preoperative sIL-2 receptor was higher and EBV positive cases in cerebrospinal fluid tended to be more common (p=0.051, p=0.086, respectively). Five of the six patients with PCNSL were treated at our hospital, four of which were treated with highly active antiretroviral treatment (HAART) and whole-brain irradiation and one with HAARA alone, resulting four with CR and one with SD. Four patients, except one who had sudden death of unknown cause, were still alive without recurrence (median observation period 44.5 months). CONCLUSION: At the moment, it is difficult to diagnose ML without brain biopsy. HIV-positive status has been regarded as a poor prognosis factor in PCNSL patients, but the prognosis seems to have improved with HAART.